Heart failure as the initial manifestation of takayasu’s arteritis - Khan, Mohd Amir; Chandrakar, Santwana Dinesh; Shetty, Varun (International Journal of Research in Medical Sciences, 2016)
Takayasu’s arteritis is a rare systemic, inflammatory large vessel vasculitis of unknown etiology that most commonly affects women of childbearing age. It is defined as granulomatous inflammation of the aorta and its major branches. We describe a 27 years old female who presented with dyspnea in the emergency medicine department of DY patil hospital, Maharashtra, India. The initial examination showed signs of heart failure along with unequal pulses bilaterally with difference in systolic BP in bilateral upper limb of more than 10 mm Hg. Patient underwent routine investigations like ECG / 2D-echo / cardiac markers. 2decho was suggestive of severe pulmonary hypertension with dilated cardiomyopathy. Further investigation in view of physical findings and 2decho report led to the diagnosis of takayasu’s arteritis.